2014
DOI: 10.1111/tpj.12533
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis STRESS RESPONSE SUPPRESSOR DEAD‐box RNA helicases are nucleolar‐ and chromocenter‐localized proteins that undergo stress‐mediated relocalization and are involved in epigenetic gene silencing

Abstract: SUMMARYDEAD-box RNA helicases are involved in many aspects of RNA metabolism and in diverse biological processes in plants. Arabidopsis thaliana mutants of two DEAD-box RNA helicases, STRESS RESPONSE SUPPRESSOR1 (STRS1) and STRS2 were previously shown to exhibit tolerance to abiotic stresses and upregulated stress-responsive gene expression. Here, we show that Arabidopsis STRS-overexpressing lines displayed a less tolerant phenotype and reduced expression of stress-induced genes confirming the STRSs as attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 120 publications
1
68
0
Order By: Relevance
“…Most of the RNA helicases may have sequence similarity or may have similar helicase core but they are functionally distinct . Besides conformational changes of RNA duplex, RNA helicases are also involved in abiotic stress responses in plants (Owttrim, 2006;Koroleva et al, 2009a;Khan et al, 2014;Liu et al, 2016). Recently, the DEAD-box RNA helicases have been extensively studied in model and crop plants to explore their functional utilities to develop multiple abiotic and biotic stress resistance.…”
Section: Rna Helicasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the RNA helicases may have sequence similarity or may have similar helicase core but they are functionally distinct . Besides conformational changes of RNA duplex, RNA helicases are also involved in abiotic stress responses in plants (Owttrim, 2006;Koroleva et al, 2009a;Khan et al, 2014;Liu et al, 2016). Recently, the DEAD-box RNA helicases have been extensively studied in model and crop plants to explore their functional utilities to develop multiple abiotic and biotic stress resistance.…”
Section: Rna Helicasesmentioning
confidence: 99%
“…Recent studies have shown that AtRH7 DEAD-box gene confers cold tolerance in Arabidopsis thaliana . Some of the DEAD-box genes mediate epigenetic gene silencing of the stress induced genes expression through RNA directed DNA methylation (RdDM) (Kant et al, 2007;Barak et al, 2014;Khan et al, 2014). Using model oilseed crop Brassica napus, our group has studied the differential expression analysis of genes involved in abiotic stresses (Havlickova et al, 2013;Keshavaiah et al, 2014).…”
Section: Abiotic Stress and The Dead-box Rna Helicasesmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Mutations in either gene caused increased tolerance to salt, osmotic and heat stresses, as well as enhancement of stress-induced gene expression, whereas overexpression yielded the opposite effect. 7 We therefore designated the genes, STRESS RESPONSE SUPPRESSOR1 (STRS1) and STRS2. We further demonstrated that STRS1 and STRS2 are part of the ABA-independent and ABA-dependent stress regulatory networks, and function to attenuate the stress-induced expression of transcriptional activator genes.…”
mentioning
confidence: 99%
“…AtHELPS seems to functions as a negative regulator during low potassium stress ). Other DEAD-box helicases have been implicated in a variety of physiological processes in plants including determination of cell fate, biotic and abiotic stress, gene silencing, and growth (Kobayashi et al 2007;Guan et al 2013;Gu et al 2014;Khan et al 2014;Tuteja et al 2014;Zhang et al 2014).…”
Section: A Devh-box Helicase Mutant Shows Increased Basal Autophagymentioning
confidence: 99%